(untitled) - Scarborough, Norman M. (Upper Saddle River, New Jersey, 2003)
The book presents the material needed to manage a small business and grow that business in a competitive world
Kinh doanh quốc tế nâng cao
Keywords: New business enterprises,New business enterprises,Small business,small business; Management,Management,Management,Management; United states,United states